Ultra-optical characterization of thin film solar cells materials using core/shell absorber layer - Ahmed Thabet; Safaa Abdelhady; Youssef Mobarak (Institute of Advanced Engineering and Science, 2022)
This paper investigates on new design of heterojunction quantum dot (HJQD) photovoltaics solar cells CdS/PbS that is based on quantum dot metallics PbS core/shell absorber layer and quantum dot window layer. It has been enhanced the performance of traditional HJQD thin film solar cells model based on quantum dot absorber layer and bulk window layer. The new design has been used sub-micro absorber layer thickness to achieve high efficiency with material reduction, low cost, and time. Metallics-semiconductor core/shell absorber layer has been succeeded for improving the optical characteristics such energy band gap and the absorption of absorber layer materials, also enhancing the performance of HJQD ITO/CdS/QDPbS/Au, sub micro thin film solar cells. Finally, it has been formulating the quantum dot (QD) metallic cores concentration effect on the absorption, energy band gap and electron-hole generation rate in absorber layers, external quantum efficiency, energy conversion efficiency, fill factor of the innovative design of HJQD cells.